Professional Development of EFL Teachers in Mexico: Examining Cross-Cultural and Global Linkages, Influences, and Outcomes - Robert A. DeVillar; Binbin Jiang (Journal of Global Initiatives, 2010)
During the past twenty years, the paradigm of professional development in U.S. education has shifted from an analyitco-incremental model to an integrative-systematic model. The integrative-systematic model focuses on the whole-scale improvement of general student performance through the articulation, implementation, and assessment of standards that apply to teachers and teacher preparation institutions as well as to students. This article addresses the basis for this paradigm shift in the U.S. and the global expansion of the professional development mandate. The authors describe the first phase of a three-year, cross-cultural professional development program involving English-as-a-Foreign Language (EFL) teachers at a private school in Mexico.